Fluorescence‐guided D3 lymphadenectomy in robotic right colectomy with complete mesocolic excision. Issue 3 (21st January 2021) - Petz, Wanda; Bertani, Emilio; Borin, Simona; Fiori, Giancarla; Ribero, Dario; Spinoglio, Giuseppe
Abstract: Background: In robotic right hemicolectomy for cancer, appropriate lymphadenectomy is essential. Visualization of draining lymph nodes and blood flow with near‐infrared (NIR) fluorescence DaVinci ® imaging system is a recent development. We present the technique of robotic right colectomy with complete mesocolic excision (CME) and D3 lymphadenectomy using Indocyanine Green (ICG) endoscopic submucosal injection to intraoperatively identify tumour lymphatic basin. Methods: The day before surgery, in patients scheduled for robotic right colectomy an endoscopic submucosal injection of 3 mg of ICG solution around the tumor is realized. Robotic right hemicolectomy is performed with suprapubic trocars layout and "bottom to up dissection", realizing a CME with central vessel ligation and D3 lymphadenectomy. Site of primary tumor and lymphatic basin are visible with the FireflyTM camera modality. Results: From July 2016 to July 2020, 85 patients received a robotic right colectomy with CME and D3 lymphadenectomy. In 50 patients, ICG submucosal injection was performed: visualisation of the site of primary tumour and of LN in the D3 area was possible in all cases; in 17/50 patients (34%), LN out from anatomical lymphatic basin were identified. No side effects were observed. Conclusions: In this series, submucosal ICG injection showed to be feasible and safe. The accuracy in identification of D3 lymphatic basin was high, thus permitting an image‐guided radical lymphadenectomy. Fluorescent technology represents an interesting innovation to ameliorate surgery of colon cancer.